EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KREATIVITAS BERFIKIR SISWA MATA PELAJARAN PKN - Dede Sopiandy, Eko Bambang Murdiansyah, Sitti Nur Wahida, Anastasia; Intan Nuraini, Melin, Miftahul Khaer (STKIP Subang, 2025)
Problem Based Learning (PBL) learning in improving creative thinking skills of class VIII A students at SMP Negeri 1 Kolaka in PPKn subjects. The method used is Classroom Action Research (PTK) which is carried out in two cycles. Data collection techniques are in the form of tests and observations. The results of the study showed that in the pre-cycle, student learning activities were classified as high at 71.87%, but the level of learning completion was not optimal. In cycle I, the level of completion reached 62.5% and increased significantly in cycle II to 93.75%. This increase shows that the PBL model can encourage active student participation, build knowledge independently, and improve creative thinking skills. Thus, the PBL model is effective as a learning approach to improve student creativity